Elemental Impurity Analysis in Five Different Types of Coffee: Assessment of Carcinogenic and Non-carcinogenic Risks - Fadime Canbolat (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
In the study, the levels of Cd, Pb, As, and Hg elemental impurities potentially present in coffee bean samples from Indonesia, Kenya, Colombia, Guatemala, and Türkiye were determined using chromatographic analysis, and the analysis results were utilized to assess the risks on human health. The risk assessment of coffee was calculated for one or three servings per day for 365 days a year. Exposure to coffee consumption was calculated according to age groups of young adults and middle-aged adults (20-65 years). When Cd, Pb, As and Hg levels in coffee samples were analyzed, Cd in coffee samples was found to be in the range of approximately 3.70 - 5.89 µg/kg, Pb in the range of 25.68-41.11 µg/kg, As in the range of 1.45-6.64 µg/kg and Hg in the range of 1.06-5.06 µg/kg. Hazard Index (HI) values for all elements in the assessment of non-carcinogenic risks were found to be <1.0. When the cancer risk (CR) value was calculated for Cd, Pb, and As, it was found that the CR value did not exceed the United States Environmental Protection Agency (USEPA) criteria in all coffee samples in both scenarios. Considering the assessment of the health risks of elemental impurities in five different coffee bean samples, it was concluded that all samples' CR and HI values did not exceed the USEPA criteria.